All genera of the infraorder Gryllidea of the world: a full list and biodiversity information on the April 2020 release of the Orthoptera Species File (OSF) - Gao, Si-Jia; Xu, Fei; Liu, Hao-Yu (Zootaxa, 2020)
According to the Orthoptera species file, there are 765 genera of the infraorder Gryllidea in the world, belonging to 2 superfamilies, 8 families, 37 subfamilies and 6159 species or subspecies in total. A complete list of all genera in the world is provided, including type species, synonyms and species richness. Through statistical analysis, there are 26 extant subfamilies, accounting for 70.27%, 692 extant genera, accounting for 90.46%, 6010 extant species or subspecies, accounting for 97.58%. At the same time, the composition characteristics of the extant genera and species or subspecies in all subfamilies: subfamily Gryllinae has the largest number of genera and species or subspecies, reaching 125 genera and 1221 species or subspecies, with the proportion of 16.34% and 20.34%, followed by subfamily Podoscrtinae, with the number of 99 genera, 770 species or subspecies, with the proportion of 12.94% and 12.83%; subfamily Gryllomiminae with the least number, the number and ratio is 1 genus, 2 species and 0.13%, 0.03%. Among all fossil genera, subfamily †Cearagryllinae is the largest, with 7 genera, 15 species. There are 21 free genera in infraorder Gryllidea, accounting for 2.75%, and 268 monotypic genera (only 1 species), accounting for 35.03%. The largest genus is Hapithus Uhler, 1864, with 209 species or subspecies.